2017
DOI: 10.1136/bmjpo-2017-000059
|View full text |Cite
|
Sign up to set email alerts
|

Impact of perinatal asphyxia on parental mental health and bonding with the infant: a questionnaire survey of Swiss parents

Abstract: ObjectiveTo compare current mental health symptoms and infant bonding in parents whose infants survived perinatal asphyxia in the last 2 years with control parents and to investigate which sociodemographic, obstetric and neonatal variables correlated with parental mental health and infant bonding in the asphyxia group.DesignCross-sectional questionnaire survey of parents whose children were registered in the Swiss national Asphyxia and Cooling register and of control parents (Post-traumatic Diagnostic Scale, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 38 publications
0
27
0
1
Order By: Relevance
“…The effect of birth asphyxia is not limited only to death but also has a short and long term neurodevelopment sequelae, including cognitive and motor disabilities which are almost untreatable[ 12 , 13 ]. Different studies showed that the survivors of asphyxia developed hypoxic-ischemic encephalopathy[ 4 , 14 , 15 ], post-traumatic stress disorders[ 16 ], neurologic disability[ 17 ], low cognitive functions[ 18 ], and neurological sequel[ 19 ]. A certain experimental study also revealed that nearly 25% of the newborns who survived birth asphyxia developed neurological disorders, such as cerebral palsy and certain neurodevelopment and learning disabilities[ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of birth asphyxia is not limited only to death but also has a short and long term neurodevelopment sequelae, including cognitive and motor disabilities which are almost untreatable[ 12 , 13 ]. Different studies showed that the survivors of asphyxia developed hypoxic-ischemic encephalopathy[ 4 , 14 , 15 ], post-traumatic stress disorders[ 16 ], neurologic disability[ 17 ], low cognitive functions[ 18 ], and neurological sequel[ 19 ]. A certain experimental study also revealed that nearly 25% of the newborns who survived birth asphyxia developed neurological disorders, such as cerebral palsy and certain neurodevelopment and learning disabilities[ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this questionnaire, the mother rates eight adjectives describing her feelings towards her infant that are indicative of mother–infant bonding 41 42. This questionnaire was translated into French 43…”
Section: Methodsmentioning
confidence: 99%
“…In this questionnaire, the mother rates (from 0 to 5) eight adjectives describing her feelings toward her infant, which is indicative of mother–infant bonding99 100 and was translated into French with good psychometric properties 101…”
Section: Methodsmentioning
confidence: 99%